Cuff-less blood pressure estimation with photoplethysmogram and electrocardiogram signals - Yang, Sen (2020)
Blood pressure (BP) measurement is an important indication of health and quality of life. However, conventional means of measurement does not provide continual monitoring of data and most of the devices used are cumbersome. Accordingly, developing a non-invasive and cuff-less method for continual BP measurement is essential.